Attendance is One of the Major Factors for Academic Performance of the Students of Elementary Classes - Majumdar, B.G.; Raychaudhuri, Amitava (INDIAN EDUCATIONAL REVIEW, 2012)
The main objectives of education, as quoted by Gen. J.J. Singh, Governor of Arunachal Pradesh, 11 September 2009 are to bring “changes not only in the amount of knowledge but also for achieving abilities to do something, to think and to acquire habits, skills and attitudes, which characterise an individual, who is socially accepted and adjusted”. Keeping these in view Sarva Shiksha Abhiyan was launched in 2001 by MHRD, Government of India with the objective of implementing scheme of ensuring education to children up to eleven years of age by 2007 and upto fourteen years of age by 2010.